ATP synthase complex and the mitochondrial permeability transition pore: poles of attraction - Chinopoulos, Christos (EMBO Rep, 2017)
The identity of the mitochondrial permeability transition (mPT) pore, a megachannel embedded in the inner membrane opened by Ca(2+), is fiercely debated. Unraveling the components structuring this pore is critical for combating diseases as diverse as neurodegeneration, cancer, autoimmunity, and myopathies in which this phenomenon is implicated. Current consensus is that the pore is formed within, or in‐between F(0)F(1) ATP synthase dimers, but not through their c‐subunit ring. Two recent studies in this issue of EMBO Reports throw more light on these aspects, one by Giorgio et al 1 showing that the β subunit of the ATP synthase harbors a Ca(2+)‐binding site responsible for triggering mPT, and the other by Bonora et al 2 demonstrating that permeability transition requires dissociation of F(0)F(1) ATP synthase dimers, albeit in a manner involving the c‐subunit ring.